Adsorption of Fluoride Ion onto Zirconyl-Impregnated Activated Carbon Prepared from Lapsi Seed Stone - Joshi, Sahira; Adhikari, Mandira; Pradhananga, Raja Ram (Journal of Nepal Chemical Society, 2013)
The potentials of activated carbon derived from Lapsi (Choerospondias axillaries) seed stone after impregnation with zirconium for adsorptive removal of fluoride is presented. Activated carbons from Lapsi seed stone were prepared by three different techniques. Firstly by directly burning in limited supply of air, secondly by treating with a mixture of conc. H2SO4 and HNO3 (in the ratio of 1:1 by weight) and thirdly by activation with zinc chloride (in the ratio of 1:1 by weight) followed by carbonization at 400°C and 500°C under nitrogen atmosphere. Thus prepared carbons were impregnated with zirconyl oxychloride and effects of pH, adsorbent dose, and contact time and adsorbate concentration for the removal of fluoride were evaluated by batch mode. The optimum pH for adsorption of fluoride was observed at pH 3-4, and a minimum contact time for the maximum defluoridation was found to be 180 min. The Langmuir and Freundlich isotherms were used to describe adsorption equilibrium. Zirconium impregnation increased the fluoride adsorption capacity of carbon to considerable extent. Among carbon prepared by three different techniques, the carbon prepared from zinc chloride activation followed by carbonization showed relatively higher fluoride adsorption capacity. From the experiment it is concluded that activated carbon prepared from Lapsi seed is an efficient, low-cost alternative to commercial activated carbon for defluoridation of water. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9330 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 13-23 Uploaded date: 12/16/2013